The impact of diabetes on postoperative outcomes following lower-extremity bypass surgery - Wallaert, Jessica B. (2012)
OBJECTIVE: The effect of diabetes type (noninsulin dependent vs insulin dependent) on outcomes after lower-extremity bypass (LEB) has not been clearly defined. Therefore, we analyzed associations between diabetes type and outcomes after LEB in patients with critical limb ischemia. METHODS: We performed a retrospective analysis of 1977 infrainguinal LEB operations done for critical limb ischemia between 2003 and 2010 within the Vascular Study Group of New England. Patients were categorized as nondiabetic (ND), noninsulin-dependent diabetic (NIDD), or insulin-dependent diabetic (IDD) based on their preoperative medication regimen. Our main outcome measures were in-hospital mortality and major adverse events (MAEs) – a composite outcome, including myocardial infarction, dysrhythmia, congestive heart failure, wound infection, renal insufficiency, and major amputation. We compared crude and adjusted rates of mortality and MAEs using logistic regression across diabetes categories. RESULTS: Overall, 41% of patients were ND, 28% were NIDD, and 31% were IDD. Crude rates of in-hospital mortality were similar across these groups (1.7% vs 3.1% vs 2.1%; P = .211). Adjusted analyses accounting for differences in patient characteristics showed that diabetes is not associated with increased risk of in-hospital mortality. However, type of diabetes was associated with a higher risk of MAEs in both crude (15.1% for ND; 21.1% for NIDD; and 25.2% for IDD; P <.001) and adjusted analyses (odds ratio for NIDD, 1.41; 95% confidence interval, 1.2–1.7; odds ratio for IDD, 1.53; 95% confidence interval, 1.3–1.8). CONCLUSIONS: Diabetes is a significant contributor to the risk of postoperative complications after LEB surgery, and insulin dependence is associated with higher risk. Quality measures aimed at limiting complications after LEB may have the most impact if these initiatives are focused on patients who are IDD.